The Hyperglycemia and Hyperketonemia Impaired Bone Microstructures: A Pilot Study in Rats - Liu, Qi; Yang, Zhou; Xie, Chuhai; Ling, Long; Hu, Hailan; Cao, Yanming; Huang, Yan; Zhu, Qingan; Hua, Yue (Frontiers in Endocrinology, 2020)
Purpose: Diabetes mellitus (DM) is the known causes of osteoporosis. Ketogenic diet (KD), an effective regimen for epilepsy, is also compromised the bone microstructures. But the similarities and differences between them is still unknown. The purpose of this study was to investigate the effects of hyperglycemia and hyperketonemia on bone in rats. Methods: Thirty male Sprague-Dawley rats were randomly divided into three groups: the sham, DM, and KD groups. The hyperglycemia was induced by streptozotocin in DM group, while the hyperketonemia was induced by feeding with the ketogenic diet (1:3 carbohydrates to fat) in KD group. The body weight, blood ketone body, and blood glucose were monitored as well as the bone length, the bone microstructures, the bone biomechanics, and histomorphology were measured in 12 weeks after intervention. Results: The body weight in DM group was significant lost compared to sham and KD groups, as well as bone length of the tibia and femur did. The blood glucose and blood ketone were noticeable increased in DM and KD rats, respectively. Microstructures and properties of cancellous bone were significantly deteriorated in both the DM and KD groups compared to sham group by decreasing the bone volume and disturbing the bone trabecula structures. While, the thickness and bone strength of cortical bone were obviously lower in the DM group than that in the sham and KD groups. The HE staining showed that bone trabecula was significantly decreased both in the DM and KD groups, and the KD rats exhibited more adipose tissue. The activity of osteoblasts was significantly decreased and the activity of the osteoclasts was remarkably increased in both KD and MD groups than those in the sham group. Conclusions: Both hyperglycemia and hyperketonemia have the adverse effects on bone. Therefore, it is worth to attention the patients with hyperketonemia and hyperketonemia in clinic.